Solitude professionnelle d’enseignants du secondaire : Relations avec le leadership du directeur d’école et leurs croyances d’autoefficacité sociale - Thibodeau Stéphane; Dussault, Marc; Frenette Éric; Royer, Nicole (Canadian Journal of Education/Revue canadienne de l’éducation, 2012)
The goal of this study is to verify a theoretical model of the relationship between the leadership of the school principal and professional loneliness of teachers and the role of social self-efficacy of teachers in this relationship. Four hundred and eighty-seven high school teachers participated to this research. Path analysis of the proposed model provides a good fit to the data. It thus shows the direct relationship between leadership and professional loneliness as the mediating role of social self-efficacy in this relationship. The results are discussed in the light of Bass’ transformational leadership theory, Bandura’s social cognitive theory of self-efficacy, Peplau and Perlman’ s cognitive approach to loneliness, and results of previous studies. Keywords : Leadership, professional loneliness, school principal, social self-efficacy, social self-efficacy beliefs, teacher